2013
DOI: 10.1002/jgrd.50315
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recombination and attachment on meteor radar diffusion coefficient profiles

Abstract: [1] Estimates of the ambipolar diffusion coefficient producedusing meteor radar echo decay times display an increasing trend below 80-85 km, which is inconsistent with a diffusion-only theory of the evolution of meteor trails. Data from the 33 MHz meteor radar at King Sejong Station, Antarctica, have been compared with observations from the Aura Earth Observing System Microwave Limb Sounder satellite instrument. It has been found that the height at which the diffusion coefficient gradient reverses follows the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…The 97 km inflection point is likely due to the suppression of diffusion of meteoric plasma outward from the trail axis by the geomagnetic field (Jones, ). In contrast, the reversal near 80 km is caused by the neutralization of meteoric plasma in addition to ambipolar diffusion (Lee et al, ; Younger et al, ). The height of the lower inflection point can be used as a tool for measuring the height of a constant density surface (Reid et al, ; Younger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The 97 km inflection point is likely due to the suppression of diffusion of meteoric plasma outward from the trail axis by the geomagnetic field (Jones, ). In contrast, the reversal near 80 km is caused by the neutralization of meteoric plasma in addition to ambipolar diffusion (Lee et al, ; Younger et al, ). The height of the lower inflection point can be used as a tool for measuring the height of a constant density surface (Reid et al, ; Younger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, further research showed that chemistry may also play a role in this trail destruction, particularly at altitudes below 83-84 km (e.g. Lee et al, 2013, and references therein, although the very high attachment rate of electrons to aerosols used in that paper is open to discussion).…”
Section: Introductionmentioning
confidence: 94%
“…This stage of ablated meteor vapour and plasma dynamics is accompanied by adiabatic (explosive) meteor trail formation with some initial radius r 0 Jones and Campbell-Brown, 2005); the process is discussed in Appendix B in the context of a "neck" of recompressed air behind the meteoroid. The explosive adiabatic formation of the initial trail with r 0 is accompanied by turbulence generated in the immediate meteor wake (T < 10 000 K), driven by the local flow field velocity, temperature, and density gradients (Lees and Hromas, 1962). This process is completed within less than the first millisecond.…”
Section: Characteristics Of Strong and Transitionally Dense Meteor Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that we do not attempt to derive temperatures from the meteor radar measured diffusion coefficients here, as for example, described in Holdsworth et al (2006), as there are significant limitations in this approach (see Lee et al, 2013;Younger et al, 2014). However, Lee et al (2016) have described a new method of estimating temperatures near the mesopause region using meteor radar observations by calibrating their meteor radar against Aura MLS temperatures.…”
Section: Meteor Radarmentioning
confidence: 99%